2011
DOI: 10.1186/1471-2229-11-64
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the rpoB-psbZ region in fern plastid genomes: notable structural rearrangements and highly variable intergenic spacers

Abstract: BackgroundThe rpoB-psbZ (BZ) region of some fern plastid genomes (plastomes) has been noted to go through considerable genomic changes. Unraveling its evolutionary dynamics across all fern lineages will lead to clarify the fundamental process shaping fern plastome structure and organization.ResultsA total of 24 fern BZ sequences were investigated with taxon sampling covering all the extant fern orders. We found that: (i) a tree fern Plagiogyria japonica contained a novel gene order that can be generated from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 70 publications
2
36
1
Order By: Relevance
“…5), suggested that the original source sequence was the trnY - trnE IGS. The 19 bp sequence found in this study is 6 bp longer than the trnY anticodon partial sequence proposed as the repeating unit origin [29]. Additionally, the 19 bp sequence had higher similarities than the 13 bp consensus sequence of the trnY anticodon loop region suggested in previous studies [29].…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…5), suggested that the original source sequence was the trnY - trnE IGS. The 19 bp sequence found in this study is 6 bp longer than the trnY anticodon partial sequence proposed as the repeating unit origin [29]. Additionally, the 19 bp sequence had higher similarities than the 13 bp consensus sequence of the trnY anticodon loop region suggested in previous studies [29].…”
Section: Discussioncontrasting
confidence: 50%
“…The lengths of trnY-trnE IGS usually less than I kb in other monilophytes [28]. This unusual trnY-trnE IGS length was also detected in E. ramosissimum , and this unique characteristic may be attributable to a repetition of the trnY anticodon loop [29].…”
Section: Introductionmentioning
confidence: 76%
“…According to Sheveleva et al [56], the presence of rpoA gene is quite variable from species to species. The membrane thylakoid gene ycf66 is absent in A. formosae [30,57,58] but remains more stable in Polytrichaceae than in ferns [59]. Only two species of bryophytes are currently known to lack the petN gene [20,21], part of the photosynthetic cytochrome b6lf complex in the chloroplast, and it is possible, according Oliver et al, that another nuclear-encoded gene product performs the same function as a subunit of the complex [20].…”
Section: Discussionmentioning
confidence: 99%
“…In P. patens, the petN-trnC region is clustered with pet genes due to an inversion of a large part of the plastome (Sugiura et al, 2003). Such inversions leading to structural rearrangements of the gene order have also been described for plastid genomes of monilophytes (Gao et al, 2011).…”
Section: Genomic Location and Promoter Analysis Of The Plastid Srp Rnasmentioning
confidence: 93%